Using Zoom Meetings in Speaking Skills of English for Nurses - Suryati, Ni Wayan Novi; Dewi, Kadek Maya Cyntia (Universitas Jambi, Indonesia, 2024)
This research aimed to analyze the use of Zoom Meetings in teaching speaking skills in English, particularly in English for Nurses (EFN) subject. The research employed a mixed-method design. There were 60 participants involved in this research. Data were collected using questionnaires and interviews. Based on the findings in the convenience aspect, 67% of participants stated strongly agree, 17% of participants agreed, and 16% disagreed on the ease of using the video conferencing feature. Furthermore, 83% of participants agreed, and 17% disagreed on the effectiveness of Zoom Meetings, which can help participants become more productive in learning EFN. In terms of the effectiveness of the use of Zoom Meetings in speaking skills, 67% of participants agreed, and 33%disagreed with this application. Additionally, the interview results also showed that participants feel much helped by having Zoom Meetings as a learning platform in learning to speak because they can interact face-to-face with the lecturer and other students. They also stated that it is helpful to increase their confidence when speaking English. However, there are also weaknesses in using Zoom Meetings in terms of Internet network constraints, which must be stable and strong. Afterward, the duration of the limited Zoom Meetings is very limited because it takes quite a long time when speaking. It indicates that the use of Zoom Meetings from the aspect of convenience, benefits, and usability of Zoom Meetings is very effective in learning, especially in learning Speaking in EFN.